Analysis of postoperative weight loss associated with prognosis after lobectomy for lung cancer. (29th September 2022) - Nakada, Takeo; Tsukamoto, Yo; Kato, Daiki; Shibazaki, Takamasa; Yabe, Mitsuo; Hirano, Jun; Ohtsuka, Takashi
Abstract: OBJECTIVES: Weight assessment is an easy-to-understand method of health checkup. The present study investigated the association between weight loss (WL) after lung cancer (LC) surgery and short–mid-term prognosis. METHODS: The data of patients who underwent radical lobectomy for primary LC were assessed between December 2017 and June 2021. Percentage weight gain or loss was determined at 3, 6 and 12 months postoperatively based on preoperative weight. The timing of decreased weight was divided into 0–3, 3–6 and 6–12 months. We also evaluated the relationship between severe WL (SWL) and prognosis. RESULTS: We reviewed 269 patients, of whom 187 (69.5%) showed WL within 1 year after surgery. The interquartile range for maximal WL was 2.0–8.2% (median 4.0%). Furthermore, we defined SWL as WL ≥8%. Twenty-five patients (9.3%) died: 9 from primary LC and 16 from non-LC causes. Cancer recurrences occurred in 45 patients (16.7%). WL occurred from 6 to 12 months postoperatively was associated with poor overall survival and recurrence-free survival ( P < 0.05, both). Body mass index <18.5 kg/m 2 and idiopathic pulmonary fibrosis were predictive factors ( P < 0.05, all). In the SWL group, overall survival, recurrence-free survival and non-cancer-specific were worse ( P = 0.001, 0.005 and 0.019, respectively). Age ≥70 years and severe postoperative complications were predictive factors for SWL ( P < 0.05, all). CONCLUSIONS: WL from 6 to 12 months postoperatively and SWL were associated with poor prognosis. Ongoing nutritional management is important to prevent life-threatening WL in patients with predictive factors. Abstract : Weight assessment is a simple and easy-to-understand method of health checkup that patients can perform by themselves.